The Influence of Physical Work Environment and Non-Physical Work Environment and Work Culture on Teacher Performance With Discipline as an Intervening Variable in High Schools of Paser District - Elli Rahmawati; Ratno Purnomo; Meirani Harsasi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of the physical work environment and non-physical work environment as well as work culture on teacher performance with discipline as an intervening variable at the Paser District Public School. The research design used in this research is descriptive quantitative. The population in this study were all teachers who taught at Paser Regency State High Schools in the Batu Sopang District area with a total of 133 people. The sampling technique used in this research used a purposive sampling technique. The results of the research show that there is an influence of the physical work environment on teacher performance with a P Value of 0.003, there is no influence of the non-physical work environment on teacher performance with a P Value of 0.028, there is a significant influence of work culture on teacher performance with a P Value of 0.023, there is a significant influence between work discipline on teacher performance with a P Value of 0.000, there is a significant influence between the physical work environment on performance through work discipline with a P Value of 0.007, there is a significant influence between the non-physical work environment on performance through work discipline and P value is 0.042, there is a significant influence between work culture on performance through work discipline with a P value of 0.023